CAVERNOUS SINUS THROMBOSIS - Sumantra, I Gede; Marzuki, Marzuki (Universitas Wijaya Kusuma Surabaya, 2014)
Cavernous sinus thrombosis (CST) is a rare diagnosis although must be included in the differential of headache. CST is either infectious or aseptic. Aseptic thrombosis usually occurs secondary to trauma or is post surgical. Sinusitis appears to be the most common cause for septic CST. Otitis media, facial cellulitis (located medial third paranasal) and odontogenic infections are also commonly implicated. Cavernous sinus thrombosis (CST) is a rare phenomenon that requires clinical suspicion and emergent imaging for correct diagnosis. Mycotic aneurysm is a rare complication of cavernous sinus thrombosis and may be treated with antibiotics, carotid ligation, internal carotid artery balloon occlusion, or Guglielmi detachable coil (GDC) embolization.